Estudo químico de Psychotria carthagenensis (Rubiaceae) e avaliação das atividades citotóxica, antioxidante e anticolinesterásica - Barros, Matheus Silva de (2022)
Psychotria carthagenensis (Rubiacea) is a shrubby species native to the Brazilian Cerrado, popularly known as carnedevaca. It is one of the main ingredients used in the hallucinogenic drink ayahuasca, which is quite common in Peru. The plant material was collected in the municipality of CorumbaíbaGO and identified as the probable cause of death of ruminants in this region. Initially, the ethanolic extract of the leaves (EEFl) and flowers (EEFf) was prepared and submitted to liquidliquid extraction, from which the fractions in hexane (FHFo and FHFl), dichloromethane (FDFo and FDFl), ethyl acetate (FAFo and FAFl) and hydroalcoholic residue (FHAFo and FHAFl) were obtained. The FDFo fraction was selected for column chromatography which resulted in six new subfractions that were analyzed by 1H, 13C and 135 DEPT NMR, from which the presence of phenolic compounds could be observed. The ethanolic extracts and fractions were submitted to antioxidant activity evaluation assays (DPPH and FRAP), and the best results were observed for the fractions FAFo and FAFl, when compared to the positive controls. These fractions showed antioxidant activity higher than 90% in the DPPH method. The samples were also submitted to acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibition assays. The fractions FAFo and FAFl presented inhibition values higher than 79% for AChE and higher than 61% for BChE, close to those of the positive controls (galantamine and rivastigmine). The extracts and fractions were also submitted to a cytotoxic activity assay using NIH/3T3 cells, and the extracts and fractions presented cytotoxic activity only at the highest concentration tested (600 µg/mL), indicating low cytotoxic potential. Among the samples tested, only the fractions FHFl and FDFl showed cytotoxicity of 59 and 41%, respectively. Thus, these results suggest that P. carthagenensis does not present compounds with cytotoxic potential in sufficient quantity that could be detected in the assay performed, but additional studies are needed for confirmation even in animal models. However, the results of AChE/BChE inhibition and antioxidant activity presented by the extracts and fractions indicate that P. carthagenensis is a promising source of compounds with potential for the development of antiAlzheimer pharmaceuticals.